THE IMPLICATION OF PERIODONTITIS TO ATHEROSCLEROSIS: ITS RELATIONSHIP WITH LIPID PROFILE AND hs-CRP SERUM CONCENTRATION - Rasmidar Samad (Faculty of Dentistry, Universitas Indonesia, 2015)
C-Reactive Protein and serum lipids are correlated with atherosclerosis. The purpose of this study was to prove that increasing level of hs-CRP and serum lipids were correlated with periodontitis. This was a cross-sectional approach with 63 samples. Periodontitis was determined if the pocket depth (PD) was more than 4 mm and the attachment loss (AL) was more than 2 mm. Serum lipids and hs-CRP was analyzed by enzymatic method and chemiluminescent (Immulite hs_CRP) alternatively. With unpaired t-test it has showed that there was a difference level of hs-CRP and total cholesterol in periodontitis and non-periodontitis. It was found that there was a significant positive correlation between PD (r=0.26), AL (r=0.25) with hs-CRP serum level; and PD (r=0.27), AL (r=0.30) with total cholesterol and LDL. It was concluded that there is a possibility that there is a relationship between periodontitis and atherosclerosis.